One- and two-dimensional finite element modelling of thaw consolidation - R. Dayarathne; B. Hawlader; Ryan Phillips; Dilan Robert (2022)
Coupled thermo-hydro-mechanical finite element (FE) modelling of thaw consolidation is presented. One-dimensional FE analyses are performed for thaw consolidation of a soil column due to self-weight and with a combination of self-weight and surcharge, with the linear and nonlinear void ratio–effective stress–hydraulic conductivity relationships of thawed soil. The nonlinear behaviour of thawed soil is modelled using a modified Drucker–Prager Cap model, while the hydraulic conductivity is varied with the void ratio. Finally, two-dimensional FE modelling of thaw consolidation around a warm pipeline buried in permafrost is performed. The rapid reduction of the void ratio with consolidation, especially at the low-stress level, results in a wide variation of hydraulic conductivity within the thawed zone. The significantly large hydraulic conductivity of soil elements along the curved thaw front, as compared to that of thaw consolidated soil, causes the flow of water along the thaw front, instead of a vertical flow, as assumed in previous 1-D thaw consolidation modelling of buried pipelines.